Growth accounting: how institutions affect Portugal's growth - Dinis, Ariane Vaz (2013)
The main objective of this Work Project (WP) is to understand whether institutional quality has been determinant to the increase of Portugal's productivity. This WP provides a sector-wise Growth Accounting exercise and analyzes the Total Factor Productivity (TFP) growth. Secondly, it uses a cross-country approach to understand which institutional indicators influence TFP growth. This WP considers, based on GMM estimation, different models to capture the causality between productivity growth and Institutional Quality. The results obtained reveal a positive relation between TFP growth and Institutional Quality.